S&K Berlaku: A Short Screenplay on Consumer Culture - Aulia Rahmadhiyan; Liem Satya Limanta (Institute of Research and Community Outreach - Petra Christian University, 2026)
In Indonesia, excessive shopping has increased due to consumer culture, which has led to the widespread use of online loans with a notably high tendency for borrowers to fail to make payments. In researching for this creative work, we tackle the problem of consumer culture and how to break free from its influence. Using Slater's (1997) and Baudrillard's (1998) theories of consumer culture as a framework, this creative work illustrates how people use online loans not only to make purchases but also to elevate their social standing and win praise from their peers. This creative work also explores the fatal consequences of using online loans, as the main character faces a series of terror after failing to repay his online loan debt and is forced into confrontation with an organ trafficking syndicate disguised as debt collectors.